Selective Removal of Water Generated during Hydrogenotrophic Methanation from Culture Medium Using Membrane Distillation - Okkyoung Choi; MinJeong Kim; Youngwook Go; Moon-Gi Hong; Bomin Kim; Yonghyun Shin; Sangho Lee; Young Gook Kim; Ji Sun Joo; Byoung Seung Jeon; Byoung-In Sang (Energies, 2019)
Methane production was carried out in two different types of reactors using a thermophilic and hydrogenotrophic methanogen, Methanothermobacter sp. KEPCO-1, which converts hydrogen and carbon dioxide into methane at 60 °C. The two reactors used for methane production were stirred-tank reactor (ST) and a bubble column reactor (BC), which were selected because they can provide a good comparison between the medium agitation type and gas−liquid mass transfer. The specific growth rate of KEPCO-1 in the ST and BC was 0.03 h−1 and 0.07 h−1, respectively. The methane conversion rate increased to 77.8 L/L/d in the ST and 19.8 L/L/d in the BC. To prevent the dilution of nutrients in the medium by the water generated during the hydrogenotrophic methanation reaction, a membrane distillation (MD) process was applied to selectively remove water from the culture medium. The MD process selectively removed only water from the medium. Fouling by KEPCO-1 had a negligible effect on flux and showed a high removal performance flux of 16.3 ± 3.1 L/m2/h. By operating the MD process in conjunction with the hydrogenotrophic methanation process, it is possible to prevent the dilution of the nutrients in the medium by the water generated during the methanation process, thereby maintaining stable microbial growth and methanation activity.